Blame It on My Parents! - Parental Heritage Influence on Iban Popular Music Consumption and Ethnic Identity Among Iban Youths in Malaysia - Ting, Su-hie; Alvin , Youri Ajan; Jerome , Collin (Journal of Ethnic and Cultural Studies, 2023)
The Iban is an indigenous group living in the Malaysian state of Sarawak, located on Borneo Kalimantan. The study examined ethnic identity and consumption of Iban pop songs by investigating the influence of half- or full-Iban parentage on knowledge, attitudes and practices of listening to Iban pop songs. Questionnaire data were collected from 189 Iban participants (21.16% half-Iban; 78.84% full-Iban). The favourite genre of Iban pop songs is ballads but 74.6% of the participants could sing the iconic Iban rock song, Biar Bekikis Bulu Betis. A majority of the Iban participants listened to Iban pop songs on YouTube channels although a fair number still used the radio and mobile phones. The participants believed that Iban songs can unite the Iban and represent the Sarawakian identity. The male participants were more familiar with Iban pop songs than the female participants. Consumption of Iban music does not differ significantly with monthly income and education level. The results showed that full-Iban participants are more interested in, knowledgeable about, and positive about Iban pop songs, compared to half-Iban participants. The full-Iban participants felt strongly that Iban songs can represent the Malaysian identity, and modern Iban culture and attain the international standard. The findings suggest that Iban parents shape their children's interest in Iban popular music by inculcating a strong Iban ethnic identity.